Managing Everyday Occupations as a Predictor of Health and Life Satisfaction Among Mothers of Children With ADHD. Issue 10 (August 2018) - Avrech Bar, Michal; Jlole Majadla, Shereen; Bart, Orit
Objective: Raising a child with special needs disturbs the balance of family life and affects mothers' everyday life. The purpose of this study was to assess the contribution of occupational competence, occupational settings, and role load to the health and life satisfaction of Arab mothers of children with and without ADHD.Method: Participants included 40 Israeli Arab women aged 25 to 40 years. Half were mothers of children with ADHD and half were mothers of children without ADHD. Data were collected by using four self-report questionnaires.Results: Occupational competence and occupational settings predicted mothers' mental health and life satisfaction. Having or not having a child with ADHD only reflects a minor contribution.Conclusion: Enhancing mothers' occupational competence and settings may increase their health and life satisfaction. This study highlights the need to focus on maternal occupational competence and settings as they affect mothers' health and well-being when providing intervention to children with ADHD.